(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article explains the diplomacy of Amir Temur and the sultans of Egypt on the basis of sources. Particular attention is paid to embassy relations, military operations and agreements between the two countries.